KONTRIBUSI DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN TENDANGAN DEPAN PADA PENCAK SILAT SMA PGRI PEKANBARU - Muhklasin, Ahmad; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on field observations and data obtained from PGRI Pekanbaru martial arts instructors, information was obtained from pencak silat fighters, most of whom did not achieve maximum performance. There are several factors and among the factors that cause the fault is the low ability of the PGRI Pekanbaru's combat kick, especially the frontal kick. The aim of this research is to discover the contribution of the muscular power of the explosive limb to the frontal kick capability in Pekanbaru PGRI Silat. The population of this study was composed of students who participated in the extracurricular activities of Pencak Silat of the PGRI Pekanbaru with 16 male athletes. The samples are part of the population that will be used as data sources in a study. Sampling is done by a total sampling technique, where the entire population is used as a sample of 16 students. The instrument in this study was the explosive power of leg muscles with broad standing jumps and the ability to kick forward. Based on the results of the research and data processing using statistical research procedures, one can conclude that, for the relation between the variables x and y, the value r = 0.293 then rxy <rtable is (0.293 <0.576), then Ha is rejected. The results of this study on the extracurricular martial arts of the pencak silat PGRI Pekanbaru have a very small ratio that is equal to 8.58%. This means that only 8.58% of the explosive power affects the frontal kick, while 91.42% is influenced by other factors. For this research to be feasible, but to get a good front kick, other factors must be used to make the relationship strongerKey Words: Muscular power of limbs, frontal kick